Impact of tooth brushing rhyme on the oral hygiene status of 6 -7 year old children - an educational intervention study - Sahiti, Putta Sai; Kamatham, Rekhalakshmi; Saikiran, Kanamarlapudi Venkata (Medicine and Pharmacy Reports, 2019)
Aim. To determine the impact of a newly composed tooth brushing rhyme on oral hygiene status of 6 to 7-year-old children. Methods. A total of 60 children in the age range of 6 to 7 years were randomly assigned to either group 1 (experimental) or group 2 (control). Group 1 children were given brushing instructions and made to memorize a newly composed tooth brushing rhyme; the control group received only routine brushing instructions. Baseline oral hygiene status of all the children was assessed using the oral hygiene index simplified (OHI-S) and its modification for primary dentition. Oral prophylaxis was performed, and OHI was further recorded at intervals of seven, 14 and 28 days for all the children. The data was tabulated, compared, and analyzed statistically. Results. There was no significant difference in the baseline OHI-S scores between the two groups (p≥0.05). However, there was a significant difference in OHI-S scores in all the considered time intervals after the intervention. Based on the two components of OHI-S, a statistically significant difference was noted only in debris scores. (7days: P=0.04, 14 days: P≤0.001, 28 days: P≤0.001) Conclusion. The newly composed tooth brushing rhyme had a significant impact on the oral hygiene scores of children, and can be recommended in the routine educational curriculum of pre-primary children.